The International Legal Framework and Social Justice: An Evaluation of the Effectiveness of Transnational Human Rights Instruments - Zholanda; Syawal, Ismi Nuris; Fadilla, Nayla Nazura (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The international legal framework is designed to protect human rights, while the question of whether it can bring about social justice is still a matter of debate. The purpose of this study is to evaluate the efficacy of transnational human rights instruments, namely the ICCPR and ICESCR, in addressing inequality and improving social welfare across various countries. In South Africa and Indonesia, effective implementation is hampered by structural and institutional constraints. The most important contribution of the study is its fusion of analyses that are legal, social, and political. Most importantly, the study examines and evaluates how applied using a qualitative evaluative research design with comparative case studies between Sweden, South Africa, and Indonesia, on human rights. The data collection methods include document analysis, interviews, and secondary data from global indices. This article's findings indicate that Sweden has managed to successfully incorporate human rights norms into the legal framework and social protection mechanisms, resulting in high attainment of social justice. Conduct empirical research into the cross-national effectiveness of human rights instruments. The implication of this study suggests that the successful implementation of international human rights instruments depends, to a large extent, on the domestic context and the institutional capacity in question. Beyond the theoretical contribution, the findings also provide practical guidance for global human rights governance. Strengthening international monitoring and reporting mechanisms, as well as aligning them with domestic institutional reforms, can serve as a roadmap for policymakers to design more effective strategies in bridging the gap between normative commitments and tangible social justice outcomes.